The Effect of Computational Methods on Abdominal Aortic Aneurysm Stresses - Altwijri, Omar; Al‐Qahtani, Mahdi; Altinawi, Amir; Javed, Ravish; Alshehri, Ryan; Aloshan, Saud; Altaiwilai, Sultan (British Journal of Healthcare and Medical Research, 2025)
Rupture of abdominal aortic aneurysms (AAA) remains a critical clinical concern, for which biomechanical metrics, particularly peak wall stress (PWS), are increasingly recognized as essential adjuncts to conventional diameter-based rupture risk criteria. Finite element analysis (FEA) provides a rigorous framework for estimating patient specific wall stresses, yet the fidelity and reproducibility of these estimates depend strongly on mesh design. This study systematically evaluates the influence of tetrahedral versus hexahedral elements on AAA wall stress using two patient-specific models implemented in ANSYS, with both configurations subjected to graded mesh refinement, identical boundary conditions, and uniform constitutive parameters to isolate element type effects. Tetrahedral meshes produced stable, repeatable PWS estimates with smooth numerical convergence across a wide range of element densities, whereas hexahedral meshes exhibited larger stress variability and stronger dependence on mesh resolution. Although hexahedral elements achieved superior geometric quality indices, they required substantially greater computational cost and showed less consistent stress convergence. Both formulations yielded comparable spatial patterns of wall stress, but tetrahedral meshes offered improved numerical robustness and computational efficiency. Overall, these findings support tetrahedral meshing as the more practical and reliable option for patient-specific AAA biomechanical workflows, particularly those prioritizing speed, automation, and clinical integration.